ANALISIS AKTIVITAS DAN SIKAP ILMIAH MAHASISWA DENGAN MODEL PENGAJARAN LANGSUNG BERBASIS INKUIRI PADA MATA KULIAH SISTEMATIKA INVERTEBRATA - Suwondo '; Elya Febrita; Ade Suryana (Program Studi Pendidikan Biologi, 2013)
This research has purpose to know the activities and scientific attitude of students with Direct Instruction based Inquiry model on Invertebrate Systematics learning. This research is a descriptive research, that was conducted from March to June 2013. The samples in this research were the students of Biology Education who take course Invertebrate Systematics in academic year 2012/2013, amount to 110 students, who divided into 3 classes. Class A amount to 46 students, class B amount to 42 students and class C amount to 22 students. Parameters measured at this research were activities and scientific attitude of students. The data retrieval activities and scientific attitude of students using observation sheets and peer assessment questionnaires. The results showed that, activities of students in good category (78.23%) and the scientific attitude of students in good category (76.88%). Invertebrate Systematics learning with Direct Instruction based Inquiry model showed an increase in the activities of students learning and scientific attitude.Keywords : Activities, scientific attitude, Direct Instruction based Inquiry model